Differences in clerkship development between public and private Brazilian medical schools: an overview - Zanolli, Mauricio Braz; Streit, Derly Silva; Maciel, Dione Tavares; Muraguchi, Evelin Massae Ogata; Martins, Milton Arruda [UNESP]; Fatima Lopes Calvo Tiberio, Iolanda [UNESP] (Bmc, 2020)
Background Around the world, it is very expensive to become a physician. Although public medical schools are less expensive than private medical schools, tuition fees are charged at public medical schools in the majority of countries. In Brazil, public medical schools, with the exception of municipal schools, are free. There has been little investigation of any differences in conditions offered by paid or free medical schools or what occurs in public and private clerkships in Brazil. We investigated the clerkship conditions offered to the students in both public and private Brazilian medical schools by gathering the opinions of clerkship coordinators and others responsible for clerkships. Methods A cross-sectional, descriptive, analytical study using an electronic questionnaire was answered by clerkship coordinators to compare the clerkships of 30 public and 38 private Brazilian medical schools from all regions of the country. The questionnaires covered various aspects of the clinical environments, student supervision, faculty development, student assessments, rotation evaluations and extracurricular activities developed by students. Results We observed significant differences between public and private medical schools in several aspects investigated. Based on the opinions of the clerkship coordinators, with the exception of access to university hospitals, which was predominantly offered by public medical schools, private medical schools offer better clerkship conditions. The main differences were related to the number of positions, infrastructure, clinical learning environments, faculty development, student assessments, rotation evaluations and students' extracurricular activities. Conclusion This is the first study comparing Brazilian medical clerkships in private and public medical schools and provides a general vision of these programmes. It is necessary to further investigate clerkship development in the Brazilian medical school system and to study the differences between private and public medical schools globally.
Keywords: Internship and residency; Schools; medical; Education; Educational measurement; Institutional evaluation; Infrastructure; Curriculum; Public medical schools; Private medical schools; Brazilian medical schools